RELATIONSHIP BETWEEN LEARNING INTENSITY, NUMERICAL SKILLS, AND EXTRACURRICULAR PARTICIPATION WITH MATHEMATICAL LEARNING OUTCOMES OF SMA NEGERI 1 PUNDONG - Lara Hikmatullah; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Low student learning outcomes are related to many factors. Learning intensity, numerical ability, and extracurricular participation are several factors related to learning outcomes. This study aims to determine the presence or absence of a positive and significant relationship between learning intensity, numerical ability, and extracurricular participation with mathematics learning outcomes of class X students in the even semester of SMA Negeri 1 Pundong, Bantul Regency in the academic year 2015/2016. SMA Negeri 1 Pundong, Bantul Regency in the 2015/2016 academic year consisted of 7 classes. Class X.1 has an average value of UAS higher than other classes so that the population in this study classes X.2 to X.7. The sampling technique uses random sampling and X.6 is chosen as the sample class. Data collection techniques using questionnaires, tests, and documentation. Data collection instruments using a list of documents, learning intensity questionnaire, numerical ability test, and learning achievement test. The research instrument test uses a validity test, reliability test, and different power test. Analysis prerequisite tests include normality test, linearity test, and independence test. Data analysis for hypothesis testing uses product-moment correlation analysis and multiple linear regression analysis. The results showed that there was a positive and significant relationship between learning intensity, numerical ability and extracurricular participation with mathematics learning outcomes. At a significant level of 5%, =3, =23,  and ,  with a double correlation coefficient R = 0.663 and a triple regression equation, that is  Relative contribution , , , with a double determination coefficient of 0.439 and its effective contribution   ,  dan